Inorganic Waste Management Strategy at Kebayoran Lama Market, Jakarta - Rizka Shafira; Dewi Elfidasari; Nunung Nurhasanah (EXSACT-A, 2025)
Research on inorganic waste management strategies at Pasar Jaya Area 11, Kebayoran Lama, Jakarta, revealed that 79% of inorganic waste (dominated by cans, cardboard, and plastic) is recyclable. However, utilization is hindered by suboptimal waste banks and insufficient 3R (Reduce, Reuse, Recycle) segregated waste facilities. A questionnaire survey of 150 respondents (75 merchants and 75 consumers) exposed regulatory knowledge gaps: only 16.7% of merchants comprehended national waste regulations (Law No. 18/2008 and Government Regulation No. 81/2012), while consumer awareness of DKI Jakarta's anti-littering regional regulation remained low (33.3%). Although 3R concepts were widely understood (merchants 100%; consumers 97.3%), implementation was constrained by inadequate infrastructure. Through mass balance analysis and strategy formulation using PROMETHEE software, priority strategies were identified: (1) Single-use plastic reduction (φ = +0.72) as the optimal solution offering high environmental impact and low cost, and (2) Economic incentives (e.g., retribution fee discounts for active recycling merchants) (φ = +0.65). Revitalizing waste banks with professional teams and adequate facilities is projected to increase waste reduction by up to 90%. Implementing these strategies requires deploying segregated waste bins, conducting waste management training, and fostering stakeholder synergy to advance circular economy principles and achieve 2030 SDGs (Goal 11: Sustainable Cities and Goal 12: Responsible Consumption and Production).